Identification of circular RNA–microRNA–messenger RNA regulatory network in hepatocellular carcinoma by integrated analysis. Issue 1 (18th July 2019) - Sun, Xiangjun; Ge, Xinfeng; Xu, Zhiyong; Chen, Dongfeng
Abstract: Background and Aim: Hepatocellular carcinoma (HCC) is the most common types of hepatic malignancies. This study aimed to better understand the pathogenesis of HCC and may help facilitate the improvement of the diagnostic of HCC. Methods: The mRNA and miRNA expression profiles of HCC, which was retrieved from The Cancer Genome Atlas database, and the circRNA expression profiles of HCC, which was retrieved from Gene Expression Omnibus database, were included in this study to perform an integrated analysis. The differentially expressed mRNAs (DEmRNAs), differentially expressed miRNAs (DEmiRNAs), and differentially expressed circRNAs (DEcircRNAs) were identified, and competing endogenous RNA (ceRNA) (DEcircRNA–DEmiRNA–DEmRNA) regulatory network was conducted. Functional annotation of host gene of DEcircRNAs and DEmRNAs in ceRNA regulatory network was performed. Quantitative real‐time polymerase chain reaction validation of the expression of the selected DEmRNAs, DEmiRNAs, and DEcircRNAs was performed. Results: A total of 2982 DEmRNAs, 144 DEmiRNAs, and 264 DEcircRNAs were obtained. The ceRNA network contained 61 circRNA–miRNA pairs and 1149 miRNA–mRNA pairs, including 48 circRNAs, 30 miRNAs, and 1149 mRNAs. Functional annotation of DEmRNAs in ceRNA regulatory network revealed that these DEmRNAs were significantly enriched in tryptophan metabolism, fatty acid metabolism, and pathways in cancer. Except for ARNT2 and hsa‐miR‐214‐3p, expression of the others in the quantitative real‐time polymerase chain reaction results was consistent with that in our integrated analysis, generally. Conclusion: We speculate that hsa_circRNA_104268/hsa‐miR‐214‐3p/E2F2, hsa_circRNA_104168/hsa‐miR‐139‐5p/HRAS, and hsa_circRNA_104769/hsa‐miR‐93‐5p/JUN interaction pairs may play a vital role in HCC. This study expected to provide a novel insight into the pathogenesis and therapy of HCC from the circRNA–miRNA–mRNA network view.